Rewriting History in Manga
XV, 191 p. 14 illus., 12 illus. in color.
Keywords: This book analyzes the role of manga (Japanese comics) within contemporary Japanese public discourse, and explores its role in propagating new perceptions regarding Japanese history. Through the analysis of a variety of cases studies ranging from nineteenth century magazines to contemporary online comics and fandom, it focuses on the representations and interpretations of history in manga, and clarifies this medium’s interrelation with historical memory and political debate. Stories for the Nation delineates alternative modes of historical memory and expression as they are manifested and contested in manga, and argues for manga's potential to influence the historical and political views of wide audiences in Japan.